2020
DOI: 10.1108/jabs-01-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Examining the antecedents and consequences of brand experience dimensions: implications for branding strategy

Abstract: Purpose The purpose of this study is to explore the impact of advertising, brand-related-stimuli, on the dimensions of sensory, emotional and intellectual brand experience. Design/methodology/approach The study is divided into two parts. In the first part, the objective is to examine antecedents to brand experience dimensions for umbrella brand and product brand using an experimental study; in the second part, the relationship among brand experience dimensions, brand experience evaluation and brand loyalty w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
0
5
0
1
Order By: Relevance
“…However, in comparison with the attention to the initial adoption, studies on continuous usage are considered less and have not been investigated deeply, even though the concept is essential to retaining existing customers which may further lead to saving of a lot of resources and increasing the profit of a company compared to gaining a new customer (Chen and Li, 2017; Cao et al , 2018; Yuan et al , 2019). This concept also showed that MP was able to satisfy the customer’s experience with the system, thereby leading to the establishment of the brand’s image in the market (Bapat, 2020). Briefly, the continuous use of MP is beneficial to both vendors and customers.…”
Section: Introductionmentioning
confidence: 99%
“…However, in comparison with the attention to the initial adoption, studies on continuous usage are considered less and have not been investigated deeply, even though the concept is essential to retaining existing customers which may further lead to saving of a lot of resources and increasing the profit of a company compared to gaining a new customer (Chen and Li, 2017; Cao et al , 2018; Yuan et al , 2019). This concept also showed that MP was able to satisfy the customer’s experience with the system, thereby leading to the establishment of the brand’s image in the market (Bapat, 2020). Briefly, the continuous use of MP is beneficial to both vendors and customers.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies are predominantly concentrating on purchasing and consumption experiences while ignoring the possible effect of pre-consumption experience on the evaluation of brand performance. In fact, the experiential component is now dominating customer-brand interface (Bapat, 2020). In addition, customers increasingly make a choice based on experiential factors rather than on functional benefits.…”
Section: The Moderating Variablementioning
confidence: 99%
“…According to Schmitt (1999), experience helps to connect a brand with a customers’ lifestyle. Brand experience can happen during media exposure, purchase or brand usage (Alba and Hutchinson, 1987; Bapat, 2020). It can lead customers to explore the flexibility and offers empowerment.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Customer experience has received remarkable attention in recent times. Brand experience has been studied from offline and online contexts (Khan et al. , 2016b; Bapat 2017, 2020).…”
Section: Introductionmentioning
confidence: 99%